Evaluation of maize (Zea mays) hybrids for leaf thermo-stability, photosynthetic rate, stem reserves and productivity under rain-dependent conditions - DWIVEDI, NEETA; NAUTIYAL, P C; SINGH, KALPANA; SINGH, ISHWAR (The Indian Journal of Agricultural Sciences, 2016)
Maize (Zea mays L.) is one of the most versatile crops probably due to its wider adaptability and photosynthetic efficiency but drought and higher temperature tolerance are prerequisite for cultivation under rain-dependent conditions. Fifteen maize hybrids were evaluated for yield and yield attributes during two consecutive years, i.e. 2011 and 2012, and heat tolerance and stem reserves (starch + sugars) during 2012. Leaf photosynthetic rate (PN) was measured during 2012 and 2013. Analysis of variance of grain yield and its attributes during two years showed significant variations in genotype (G), year of cultivation (Y) and their interaction (G × Y). Tasseling and silking intervals were least in PHM-1 and Parakash during both the years. Leaf relative injury index (RI) varied between 40% in both Parakash and PHM-1, and 74% in HQPM-1. Thus, hybrids were classified based on RI values such as tolerant (RI between 40 and 49%), moderately tolerant (RI between 50 and 59%) and susceptible (RIâ‰¥60). In general, PN enhanced from vegetative to anthesis and thereafter declined during grain filling stages. This was attributed to reproductive sink-driven demand. Stem reserves (non-structural carbohydrates) were higher in Parakash, HQPM 7 and JH-3459. In addition, grain protein and starch contents during milking stage were higher in DHM-117, Parakash and DHM-3. Average values of biomass and grain yields recorded during two consecutive years ranged between 1 874 and 4 769 g/m2, and 809 and 1 669 g/m2, respectively. Also, associations between various attributes of grain yield, photosynthesis, leaf temperature, RI and stem reserves were established, and potential hybrids were identified. Especially, hybrids Parakash and PHM-1 were found efficient in most of the parameters studied, such as, heat tolerance, lesser tassling and silking interval, relatively lower stem diameter at final harvest, higher stem reserves, PN, 1 000-seed mass, HI, grain and biomass yields.